Influence of customization and light-curing device on the bond strength of glass fiber posts - in vitro study - Gustavo do Prado SCHOENHALS; Larissa Pinceli CHAVES; Fabiana Scarparo NAUFEL (Universidade Estadual Paulista, 2022)
Abstract Introduction Endodontically treated teeth are usually affected by extensive structure loss requiring the use of intraradicular posts to provide retention and restoration. Objective An in vitro assessment was performed on the bonding of glass fiber posts to the root dentin. Material and method Ninety (n = 10) single bovine roots were used in a 3 x 3 x 3 factorial study with subdivided plots: post customization varying the presence and type of resin (without customization, conventional resin, and Bulk Fill resin), light-curing device (Valo, Radii-Cal, Rainbow), and root third (cervical, middle, and apical). Result For the customization factor, Tukey's test (5%) showed the superiority of the Bulk Fill (8.16 MPa) and Z350 (7.40 MPa) groups compared to the control group (4.92 MPa), without differing from each other. All light-curing devices differed, showing the superiority of Valo (9.36 MPa), Radii (6.96 MPa) as an intermediate, and the inferiority of Rainbow (4.17 MPa). The cervical root third (7.81 MPa) was superior, the apical third was inferior (5.80 MPa), and the middle third (6.88 MPa) was an intermediate without differing from the others. Conclusion The customization of glass fiber posts increases the bond strength to the root dentin, regardless of the resin used. There was a compromise in the apical third and when using light-curing devices with lower light intensity.